Protocol for high-efficiency generation of iPSCs stably expressing Cas9-EGFP using the selection by essential gene exon knockin method - Yao Zhang; Hao Yang; Yuan Yang; Zijun Lu; Lokyu Cheng; Hongmei Tan; Joe Z. Zhang (STAR Protocols)
Summary: CRISPR-Cas9 is widely used for genome editing. However, Cas9 silencing occurs during the directed differentiation of induced pluripotent stem cells (iPSCs), even when it is inserted into the safe harbor locus. Here, we generate iPSC-Cas9-EGFP using selection by essential gene exon knockin technology. We describe steps for inserting the Cas9-EGFP into exon 9 of GAPDH, bypassing Cas9 silencing. We then detail procedures for Cas9 function validation.For complete details on the use and execution of this protocol, please refer to Zhang et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.